Las adaptaciones curriculares para los estudiantes con necesidades educativas especiales asociadas al trastorno del espectro autista de la unidad educativa ecomundo de la ciudad de Babahoyo - Ochoa Carrión, Gladys (2017)
This research is correlational descriptive. For this study is considered the theoretical bases of special educational needs, the pedagogical autisms spectrum disorder studied from the clinical until the pedagogy field, the curricular adaptations and the legal basis under the international and national context, which justifies the attention and the pedagogies supports that facilitate the teaching-learning process of students with special educational needs involved in the curriculum. The methodological process of this research encompasses a mixed approach. In order to obtain the information, the field research was applied, namely the data are collected through the techniques of the survey and observation within the educational context. The results allowed us to arrive at the analysis that based the solution proposal………..